Islam in South Africa: mosques, imams, and sermons - Tayob, Abdulkader (Religion in Africa, 1999)
''Judicious juggling of insider and outsider perspectives. [Tayob] brings real knowledge and experience of South African Islam. . . . Anyone interested in religion in the South African context as well as those interested in Islam in different contexts should be interested in this book